Роль ризик-менеджменту при оцінці фінансової стійкості підприємства - Качула, Світлана Валентинівна; Kachula, Svitlana; Півкач, Сніжана Василівна; Pivkach, Snizhana (НАУКОВО-ОСВІТНІЙ ІННОВАЦІЙНИЙ ЦЕНТР СУСПІЛЬНИХ ТРАНСФОРМАЦІЙ. м. Чернігів, 2023)
Досліджено фінансову стійкість підприємства та роль ризик-менеджменту при її оцінці. Дослідження ґрунтується на принципах системно-структурного аналізу, що базується на застосуванні методів порівняння та узагальнення, наукового аналізу та синтезу до вивчення характеристик діяльності підприємств. Встановлено, що управління фінансовою стійкістю підприємства є важливим завданням для забезпечення його успішної діяльності та виживання в змінних умовах ринку. Узагальнено, що оцінка фінансового стану підприємства - це складний процес, і не існує одного найбільш повного та інформативного методу, оскільки його вибір залежить від конкретних обставин, цілей аналізу та доступності даних підприємства. Встановлено, що ризик-менеджмент є важливою складовою процесу оцінки фінансової стійкості підприємства, оскільки допомагає захищати його від негативних впливів ризиків та забезпечує стабільність та стійкість фінансової діяльності. The financial stability of the enterprise and the role of risk management in its assessment are studied. The research is based on the principles of system-structural analysis, which is based on the application of methods of comparison and generalization, scientific analysis and synthesis to the study of the characteristics of enterprise activity. The financial indicators and coefficients used to assess the level of financial stability of the enterprise are characterized. It was established that the management of the financial stability of the enterprise is an important task for ensuring its successful operation and survival in changing market conditions. The methods of managing the financial stability of the enterprise, which can be used separately or in combination to ensure the financial stability of the enterprise in various market conditions and economic circumstances, are considered. In general, the assessment of the financial condition of the enterprise is a complex process, and there is no single most complete and informative method, since its choice depends on the specific circumstances, the goals of the analysis, and the availability of enterprise data. The key role of risk management in assessing the financial stability of the enterprise is outlined. Risk management is aimed at reducing and controlling risks that may threaten the financial stability of the enterprise. Active management of financial risks, such as currency risk, sudden changes in prices, interest rates, etc., allows to reduce possible negative consequences on the sustainability and long-term development of the enterprise. Correctly configured risk management can help the company avoid crisis situations and ensure stable growth. Implementation of risk management strategies will help reduce the negative impact of financial risks on the company's activities. The application of effective measures to assess risk protection is an effective way to ensure the financial stability of the enterprise. It has been established that risk management is an important component of the process of assessing the financial stability of an enterprise, as it helps to protect it from the negative effects of risks and ensures the stability and sustainability of financial activities.
The role of risk management in assessing the financial stability of the enterprise
Keywords: стійкість; stability; підприємство; enterprise; фінансова стійкість; financial stability; показники фінансової стійкості; indicators of financial stability; коефіцієнти фінансової стійкості; coefficients of financial stability; ризик-менеджмент; risk management; ризикозахищеність; risk protection